Duration of SARS-CoV-2 RNA detection in COVID-19 patients in home isolation, Rhineland-Palatinate, Germany, 2020: an interval-censored survival analysis - Omar, Sarah; Bartz, Christoph; Becker, Sabine; Basenach, Silke; Pfeifer, Sandra; Trapp, Corinna; Hamm, Hildegard; Schlichting, Hans Christoph; Friederichs, Magdalena; Koch, Ulrich; Jestrabek, Christian; Hilger, Ernst; et al. (Eurosurveillance, 2020)
We analysed consecutive RT-qPCR results of 537 symptomatic coronavirus disease (COVID-19) patients in home quarantine. Respectively 2, 3, and 4 weeks after symptom onset, 50%, 25% and 10% of patients had detectable RNA from severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). In patients with mild COVID-19, RNA detection is likely to outlast currently known periods of infectiousness by far and fixed time periods seem more appropriate in determining the length of home isolation than laboratory-based approaches.
Gesehen am 26.10.2020